Relationship between vitamin D3 deficiency and polycystic ovarian syndrome - Elsadany, Esraa B.; Elshwaikh, Shereef L.; Borg, Hesham M.; Alghorab, Nagwa M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Vitamin D3 (VD3), a seco-steroid that is synthesized in skin and sequentially metabolized in liver and kidneys in humans, has been well-known for its function in maintaining calcium and phosphorus homeostasis and promoting bone mineralization. Polycystic ovary syndrome (PCOS) is a common cause of ovarian dysfunction in women with anovulation. Aim of this study is to show and evaluate VD3 level in women who are suffering from polycystic ovarian syndrome. Methods: This study was conducted on 200 women; group A: (study group) 100 infertile women who were suffering from PCOS and group B: (control group) 100 patients were selected with other cause of infertility than PCOS. US examination, hormonal profile (FSH, LH, AMH, TSH and prolactin level) and laboratory assay of serum VD3 level (postmenstrual) were done for every patient to evaluate relationship between VD3 deficiency and PCOS patients. Results: There was a significant relationship between group A compared to group B as regards irregular menstrual cycle, clinical hyperandrogenism, LH/FSH ratio and AMH. There was no significant difference between both groups as regards TSH, prolactin and VD3 level. VD was deficient in both groups as it was lower than normal level. There was a negative significant correlation between VD3 level and both hyperandrogenism and AMH. Conclusions: There was VD3 deficiency in PCO patients and infertile cases due to another factor, and negative significant correlation between VD3 level and clinical hyperandrogenism, LH/FSH ratio, menstrual cycle and AMH.